Boosted by closure! Regulatory focus predicts motivation and task persistence in the aftermath of task‐unrelated goal closure. (26th September 2022) - Lalot, Fanny; Gollwitzer, Peter M.; Quiamzade, Alain; Oettingen, Gabriele
Abstract: Past research has found that regulatory closure, that is, successful goal striving regulated either under a promotion or prevention focus, has important consequences in terms of motivational activation and mobilisation of cognitive resources in subsequent tasks, but it mostly investigated motivation in the same or similar tasks to the one for which closure was achieved. Drawing from an energisation‐deactivation hypothesis, we investigated the effect of closure on performance and persistence in unrelated subsequent cognitive tasks. Across four studies, we found that promotion closure had an energising effect leading to: quicker decision times in lexical tasks (Studies 1–2), increased persistence and greater originality (Study 3), and greater visuospatial memory performance (Study 4). In contrast, prevention closure had a deactivating effect leading to reduced performance and persistence. No systematic differences arose in situations of non‐closure. We discuss results and implications with respect to both regulatory closure and regulatory fit theoretical approaches.